A Communication Performance Evaluation on Smoothing Power Fluctuations Based on Demand Response Control of Thermostatically-controlled Appliances. (August 2015) - Wei, Wenting; Wang, Dan; Jia, Hongjie; Wang, Ran; Qi, Yebai; Fan, Menghua; Meng, Xiaoli
Abstract: Cyber security problem in energy system has been paid more and more attention recently. In this paper, impact of the packet loss and bit errors in the communication process on the performance of demand response was evaluated. Thermodynamic modelling mechanism of the typical electric heat pumps was first discussed. And, a novel heat pump demand response control strategy based on Optimal Temperature Regulation (OTR) was proposed. The control strategy was then applied to balance the power fluctuations caused by renewable energy. Packet loss and bit errors in the signal transmission were discussed, and their impact on the performance of the control strategy was analysed. Finally, case studies were used to validate the given method.